Functions with average and bounded motions of a forced discontinuous oscillator - Enguiça, Ricardo (2019)
In this paper we prove the existence of bounded solutions in the real line for the equation u+ sign( u) = p( t), where p is a function with average. Some useful density results for the space of functions with zero average are also obtained.